IMPLEMENTASI INKUIRI TERBIMBING BERBASIS LESSON STUDY UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS DAN HASIL BELAJAR SISWA KELAS X IPA 4 SMA BRAWIJAYA SMART SCHOOL MALANG - Azizah, Ardiani Samti Nur (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2014)
Implementation of guided inquiry learning in SMA BSS Malang to make the teaching and learning process focus on the students themselves, so that student can gain the concept from their own experience and apply it in everyday life to make them hopefully improve their the capability of critical thinking and achievements. This project is a classroom action research carried out in two cycles – each cycle consists of five meetings. The results of the observation on critical thinking ability were in the form of scores based on critical thinking rubrics. The results rated based on the cognitive learning were in the form of test results, while the affective test results were gained by observing students’ attitude, and the psychomotor test results were scored based on the students’ practical work in the laboratory. The results of the study demonstrated that based on each indicator, the students’ capability of critical thinking increased from the first to the second cycle. The results assessed based on the cognitive indicator, affective indicator and psychomotor indicator also increase.  Keywords: inquiry learning, critical thinking, achievements of students